Wave Attenuation Over Mangroves in the Nanliu Delta, China - Zhou, Xiaoyan; Dai, Zhijun; Pang, Wenhong; Wang, Jie; Long, Chuqi (Frontiers in Marine Science, 2022)
Mangrove forests grow in tropical and subtropical coastlines and play a significant role in reducing hydrodynamic energy. However, little information is known about the mechanism of wave attenuation caused by mangroves of different ages, even though the effects of mangroves on wave damping have received widespread concern. Here, a series of systemic biohydrological data were collected along a cross-shore transect through mangroves with different ages of native Aegiceras corniculatum (AC) distribution in the Nanliu Delta of China and were analyzed to investigate wave attenuation over mangroves during different tidal conditions. The results showed that the wave height decreased nearly 58.33%, with a transport distance of 275 m in the AC seedling-sapling region, and approximately 80%, with a transport distance of 1000 m in the sapling-adult region, on average. The largest wave height attenuation rate of 3×10-3 was found in the measured time period and occurred in the seedling-sapling section during the neap tide, while the sapling-adult region had a basically constant reduction rate of 0.8×10-3 under changing tidal conditions. Moreover, the drag coefficient calculation indicated that an AC seedling with a height of nearly 0.55 m was more effective in attenuating wave energy than the stem part of a grown tree with a height of nearly 1.2 m. AC seedlings and saplings have significant impacts on wave damping, even though the stem part of an adult AC could produce a decline in wave energy. Moreover, differences in the drag coefficient caused by stems and canopies were responsible for wave attenuation, and the degree of AC inundation volume induced by water level fluctuation might affect the wave damping effect. Our results documented distinct differences in the wave attenuation process by mangroves of different ages, which can inform superior designs of mangroves along coasts against a background of sea-level rise and the occurrence of frequent typhoons.